Diffuse large B-cell lymphoma as an extra-hepatic manifestation of hepatitis C and co-infection of helicobacter pylori: A case report - Kumar, Naresh; Abbasi, Amanullah; Hussain, Sana Muhammad; Mahmood, Aysal; Talreja, Kanhiyalal (Journal of the Pakistan Medical Association, 2024)
Along with infecting hepatocytes, the Hepatitis C virus (HCV) is also a lymphotropic virus. Chronic HCV infection can mutate the Bcl2, a proto-oncogene that inhibits apoptosis. This causes continuous stimulation of B lymphocytes, which results in clonal growth of these immunoglobulin-producing cells. In Western countries, there is a well-documented link between HCV and lymphoproliferative illness. HCV and Non-Hodgkin lymphoma (NHL) have been found to be significantly correlated in Europe, Japan, and the southern United States. There, however, has been no association found in central and northern Europe, the northwestern United States, and some Asian countries. A literature deficit exists in South Asia about the incidence of HCV infection in lymphoma patients. Here, the first documented instance of Diffuse Large B-cell NHL (germinal center type) is reported in a 35-year-old patient. —Continue